Representative experimental design issues in observing golfer pre-performance routine behaviour - Cotterill, S. T.; Sanders, R.; Collins, D. (International Journal of Sport Psychology, 2010)
The representative experimental design of many previous studies exploring the nature of pre-performance routine usage in golf has been limited by flaws in research design. The purpose of this study was to ascertain whether the use of a fullswing golf simulator could provide an ecologically valid alternative to lab-based experimental designs. Participants were six elite male golfers (mean age = 22.5yrs, s = 3.3 years; mean handicap = +1, s = 1; mean years playing = 8.63, s = 5.21) who were required to play in three conditions: simulated; practice; and competition. A one-way, within-participant MANOVA was conducted investigating whether significant differences existed in the temporal characteristics of the behavioural categories (head, club, posture, still) within the routines across the three conditions. Four dependent variables relating to category of behaviour were used: head, club, posture and still. The independent variable was the condition. No significant differences were identified (participant one F3,144, = .74, P = 0.66; participant two F3,144, = 1.52, P = 0.16; participant three F3,144 = 1.54, P = 0.16; participant four F3,144 = 0.74, P = 0.66; participant five F3,144 = 0.88, P = 0.54; participant six F3,144 = 1.72, P = 0.10) for any of the dependent variables, within participant, across conditions. The results suggest that the use of environmental simulators in golf could offer the opportunity to maximise the ecological validity of experimental designs, allowing the researcher to understand more fully the strategies used by the golfer in the competitive environment.